Parvovirus equino : nuevos hallazgos en caballos de Argentina - Vissani, Maria Aldana; Tordoya, Maria Silvia; Olguin Perglione, Cecilia; Alamos, Florencia; Ruiz, Vanesa (Universidad Nacional del Nordeste, 2026)
Poster